2019
DOI: 10.3311/ppch.13389
|View full text |Cite
|
Sign up to set email alerts
|

Processing Efficiency, Simulation and Enzyme Activities Analysis of an Air-Lift Multilevel Circulation Membrane Bioreactor (AMCMBR) on Marine Domestic Sewage Treatment

Abstract: The implementation of latest International Maritime Organization emission standard raised stringent requirements for marine domestic sewage discharge. In this study, an air-lift multilevel circulation membrane reactor (AMCMBR) was operated to analyze effects of various ecological factors on effluent of marine domestic sewage. Back-propagation (BP)-Artificial Neural Network (ANN) was used to simulate effect of each ecological factor on reactor performance. The activities of four enzymes were investigated to rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Cai et al [85] conducted an aerobic-anaerobic micro-sludge MBR (O-AMSMBR) to study the effect of pH on pollutant removal performance of a reactor using Wavelet Neural Network (WNN) and BPNN models and showed that pH is a key factor affecting the COD and TN removal efficiencies of O-AMSMBR. To optimize the processing efficiency of MBRs, they further studied the effects of various ecological factors on effluent marine domestic sewage by implementing an air-lift multilevel circulation MBR and analyzed their impacts on the O-AMSMBR performance using the BPNN model [86]. The results show that the order of relative importance for the ecological factors is pH ≈ MLSS > HRT > COD, which indicates that pH is significant and should be considered in implementing AI models to evaluate the effectiveness of MBR systems.…”
Section: Laboratory-scale Researchmentioning
confidence: 99%
“…Cai et al [85] conducted an aerobic-anaerobic micro-sludge MBR (O-AMSMBR) to study the effect of pH on pollutant removal performance of a reactor using Wavelet Neural Network (WNN) and BPNN models and showed that pH is a key factor affecting the COD and TN removal efficiencies of O-AMSMBR. To optimize the processing efficiency of MBRs, they further studied the effects of various ecological factors on effluent marine domestic sewage by implementing an air-lift multilevel circulation MBR and analyzed their impacts on the O-AMSMBR performance using the BPNN model [86]. The results show that the order of relative importance for the ecological factors is pH ≈ MLSS > HRT > COD, which indicates that pH is significant and should be considered in implementing AI models to evaluate the effectiveness of MBR systems.…”
Section: Laboratory-scale Researchmentioning
confidence: 99%
“…Over recent years, ANNs have been successfully applied to the modelling and control of various biological processes [12][13][14][15][16]. ANNs are now the most popular artificial learning tools in biotechnology, with applications ranging from pattern recognition in chromatographic spectra and expression profiles to functional analyses of genomic and proteomic sequences [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate Reductase is the principal limiting step of denitrification. Therefore, taking this enzymatic activity as an indicator can present the denitrification ability of wastewater treatment plants [23]. For pollutant decomposition, microorganisms present in activated sludge play vital role.…”
Section: Introductionmentioning
confidence: 99%